2014
DOI: 10.4103/1817-1745.131473
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of parent reported quality of life in children with epilepsy from Northern India: A cross-sectional study

Abstract: Objective:The objective of the following study is to assess parent reported quality of life (QOL) in children with epilepsy and to assess the demographic and clinical factors, which influence the QOL in children with epilepsy.Study Participants:We consecutively enrolled 40 children aged from 2 years to 14 years with active epilepsy who had undergone a comprehensive evaluation for epilepsy.Materials and Methods:Parents were enquired on baseline demographic variables including age, gender, socio-economic status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 10 publications
4
19
1
Order By: Relevance
“…These results are in concordance with Monir et al (5) from Egypt, who reported that epileptic children with generalized seizures have significantly lower HRQOL than those with partial seizures. However, an Indian study by Arya et al (31) found no significant difference between types of seizures and HRQOL scores. Another study from India, by Aggarwal et al (28), reported that children with partial seizures are significantly compromised in total HRQOL than generalized seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in concordance with Monir et al (5) from Egypt, who reported that epileptic children with generalized seizures have significantly lower HRQOL than those with partial seizures. However, an Indian study by Arya et al (31) found no significant difference between types of seizures and HRQOL scores. Another study from India, by Aggarwal et al (28), reported that children with partial seizures are significantly compromised in total HRQOL than generalized seizures.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the studies conducted by Aggarwal et al (28) and Nadkarni et al (30), where no significant sex difference was observed in HRQOL. However, a study conducted by Arya et al (31) observed that girls outperformed in physical, emotional, social, and psychosocial domains of HRQOL. This might be due to the small sample size (n = 102) and use of a different HRQOL assessment measure in that study.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently used generic QoL instruments were the Pediatric Quality of Life Inventory (PedsQL) or an adapted version of the PedsQL (six studies), 12,15,20,21,35,36 the Short-form 36 (SF-36; two studies), 14,34 the Impact of Childhood Illness scale (two studies), 25,28 the Child Health Questionnaire-Parent Form (one study), 26 the DISAB-KIDS chronic generic model (one study) 31 and the KINDL questionnaire (one study). 27 Disease-specific questionnaires included the Paediatric Asthma Quality of Life Questionnaire (six studies), [6][7][8][9][10][11] the Quality of Life in Children with Epilepsy (QOLCE) questionnaire (five studies), 16,17,24,26,29 the Quality of Life in Epilepsy Inventory for Adolescents (QOLIE-AD-48; three studies), 18,19,27 the PedsQL T1DM module (two studies), 32,33 the Diabetes Quality of Life for Youth short form (one study), 30 the Impact of Epilepsy Schedule (one study) 22 and the Epilepsy and Children questionnaire (one study). 23 Single-domain SES factors included household income (11 studies), [6][7][8]11,[14][15][16]22,26,29,…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…27 Disease-specific questionnaires included the Paediatric Asthma Quality of Life Questionnaire (six studies), [6][7][8][9][10][11] the Quality of Life in Children with Epilepsy (QOLCE) questionnaire (five studies), 16,17,24,26,29 the Quality of Life in Epilepsy Inventory for Adolescents (QOLIE-AD-48; three studies), 18,19,27 the PedsQL T1DM module (two studies), 32,33 the Diabetes Quality of Life for Youth short form (one study), 30 the Impact of Epilepsy Schedule (one study) 22 and the Epilepsy and Children questionnaire (one study). 23 Single-domain SES factors included household income (11 studies), [6][7][8]11,[14][15][16]22,26,29,30 mother's education (15 studies), 6,[9][10][11][12]16,17,21,22,24,25,29,31,34,36 father's education (11 studies),…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation